Răspuns :
Răspuns:
[tex] \frac{x}{4} + 3 \sqrt{2} = 4 \sqrt{2} - \frac{3}{2} + 3 \sqrt{2} \\ \frac{x}{4} + \frac{3 \times 2}{2 \times 2} = 4 \sqrt{2} + 3 \sqrt{2 } - 3 \sqrt{2 } \\ = 4 \sqrt{2} \\ \frac{x}{4} = \frac{4 \times 4 \sqrt{2} }{4} - \frac{6}{4} \\ x = 16 \sqrt{2} - 6[/tex]
Explicație pas cu pas:
\frac{x}{4} + 3 \sqrt{2} = 4 \sqrt{2} - \frac{3}{2} + 3 \sqrt{2} \\ \frac{x}{4} + \frac{3 \times 2}{2 \times 2} = 4 \sqrt{2} + 3 \sqrt{2 } - 3 \sqrt{2 } \\ = 4 \sqrt{2} \\ \frac{x}{4} = \frac{4 \times 4 \sqrt{2} }{4} - \frac{6}{4} \\ x = 16 \sqrt{2} - 6